(untitled) (Global Scientific Review, 2023)
This article describes the innovative products offered to the world markets by large companies operating in developed countries, as a result of which companies and investments in countries, and provides relevant analysis and recommendations on this topic and creating a positive investment climate should not be interpreted as a key process in the globalization of the economy, and as a result, the expansion of access to investment resources, which in turn will increase competition among investors. If we want to increase the volume of foreign investment, it is necessary to increase the investment potential of enterprises.